2023
DOI: 10.1155/2023/5157417
|View full text |Cite
|
Sign up to set email alerts
|

Enriched Environment Attenuates Ferroptosis after Cerebral Ischemia/Reperfusion Injury via the HIF-1α-ACSL4 Pathway

Abstract: Enriched environment (EE) has been proven to be an effective intervention strategy which can improve neurofunctional recovery following cerebral ischemia/reperfusion (I/R) injury. However, it still needs further investigation for the underlying mechanisms. Recently, it has been shown that ferroptosis played an essential role in the pathophysiological development of ischemic stroke (IS). This study is aimed at investigating whether EE plays a neuroprotective role by attenuating ferroptosis after cerebral I/R in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…The increase of HIF-1α protein was also observed in mice and primate brains after experimental cerebral ischemia (Speer et al 2013 ), which might account for the early neuroprotective role of HIF-1α (Cui et al 2021 ). As shown in a recent study, enriched environment (EE) promoted HIF-1α expression and thus inhibited ACSL4 expression at the transcriptional level, ultimately acting to inhibit ferroptosis in MCAO/R rats (Liu et al 2023b ).…”
Section: Therapeutic Targets For Ferroptosis In Ischemic Strokementioning
confidence: 95%
See 1 more Smart Citation
“…The increase of HIF-1α protein was also observed in mice and primate brains after experimental cerebral ischemia (Speer et al 2013 ), which might account for the early neuroprotective role of HIF-1α (Cui et al 2021 ). As shown in a recent study, enriched environment (EE) promoted HIF-1α expression and thus inhibited ACSL4 expression at the transcriptional level, ultimately acting to inhibit ferroptosis in MCAO/R rats (Liu et al 2023b ).…”
Section: Therapeutic Targets For Ferroptosis In Ischemic Strokementioning
confidence: 95%
“…It was demonstrated that PIO could decrease infarct volume and improve the neurological score of transient MCAO mice (Jin et al 2021 ). Reduction in infarct volume and inflammation as well as improvement in neurological function were observed during the treatment with PIO of rats before or after MCAO (Liu et al 2023b ). As a synthetic agonist of proliferation-activated receptor γ (PPARγ), TZDs exhibited no correlation between their anti-ferroptosis ability and PPAR-γ-mediated gene transcription (Doll et al 2017 ).…”
Section: Therapeutic Targets For Ferroptosis In Ischemic Strokementioning
confidence: 99%
“…Cerebral stroke is a devastating and debilitating cerebrovascular disease, that causes high disability and mortality, and has emerged as one of the major public health issues around the world ( 1 , 2 , 3 ). More than 80% of cerebral strokes are ischemic stroke ( 4 , 5 , 6 ).…”
mentioning
confidence: 99%